Adipose tissue at entheses: the rheumatological implications of its distribution. A potential site of pain and stress dissipation?. Issue 12 (16th November 2004) - Benjamin, M; Redman, S; Milz, S; Büttner, A; Amin, A; Moriggl, B; Brenner, E; Emery, P; McGonagle, D; Bydder, G
Abstract : Objectives: To describe the distribution of adipose tissue within and adjacent to entheses in order to assess its functional significance at attachment sites. Methods: Entheses were removed from 29 different sites in the limbs of formalin fixed, elderly, dissecting room cadavers and the samples prepared for paraffin and/or methylmethacrylate histology. Entheses from four young volunteers with no history of significant musculoskeletal injury were examined by magnetic resonance imaging using T1 weighted sequences. Results: Adipose tissue was present at several different sites at numerous entheses. Many tendons/ligaments lay on a bed of well vascularised, highly innervated, "insertional angle fat". Endotenon fat was striking between fascicles, where entheses flared out at their attachments. It was also characteristic of the epitenon, where it occurred in conjunction with lamellated and Pacinian corpuscles. Fat filled, meniscoid folds often protruded into joint cavities, immediately adjacent to attachment sites. Conclusion: Adipose tissue is a common feature of normal entheses and should not be regarded as a sign of degeneration. It contributes to the increase in surface area of attachment sites, promotes movement between tendon/ligament and bone, and forms part of an enthesis organ that dissipates stress. The presence of numerous nerve endings in fat at attachment sites suggests that it has a mechanosensory role and this could account for the rich innervation of many entheses. Because damage to fat is known to lead to considerable joint pain, our findings may be important for understanding the site of pain in enthesopathies.